Functional Forms and the Demand for Meat in the United States: A Comment - Huang, Cliff J.; Grawe, Oliver R. (The Review of Economics and Statistics, 1980)
Box, George E. P., and David R. Cox, An Analysis of Transformations, Journal of the Royal Statistical Society, series B, 26 (Apr. 1964), 211-243. Boyes, W. J., An Application of Specification Error Tests-The Liquidity Trap, Manchester School of Economics and Social Studies (1978), 139-151. Chang, Hui-shyong, Forms and the Demand for Meat in the United States, this REVIEW 59 (Aug. 1977), 355-359. Greenfield, J. N., Effects of Price Changes on the Demand for Meat, Monthly Bulletin of Agricultural Economics and Statistics 23(12) (1974), 1-8. Ramsey, James B., Limiting Functional Forms for Demand Functions: Tests of Some Specific Hypotheses, this REVIEW 56 (1974), 468-477.